Корпоративне управління сільськогосподарськими підприємствами холдингового типу - Lopatynskyi, Yurii; Белей (Belei), Cвітлана (Svitlana); Kobelia, Zoriana (My University, 2023)
У статті узагальнено сутність поняття "корпоративне управління" на основі різних трактувань. Досліджено тео-ретичні основи корпоративного управління та з'ясовано, що корпоративне управління є широко досліджуваною га-луззю, а вченими напрацьовані різноманітні дефініції цього поняття. Визначено, що сільськогосподарські підприєм-ства холдингового типу — така організаційно-правова форма ведення бізнесу, яка дозволяє практично без обмеженьмаксимально залучати ресурси для свого розвитку. Розглянуто теоретичні засади розвитку корпоративних процесівв аграрному секторі. Обгрунтовано важливість аграрного корпоративного сектора для національного господарсь-кого комплексу країни. Окреслено структурні елементи корпоративного управління сільськогосподарськими підприє-мствами холдингового типу. З метою формування ефективного корпоративного управління сільськогосподарськи-ми підприємствами холдингового типу запропоновано застосування принципів, що передбачають формування цілейі завдань аналізу, плану і програми його проведення на підставі вибору пріоритетності критеріїв та їх показників(регламентованих у нормативно-правових документах і стандартах), з урахуванням впливу зовнішніх і внутрішніхфакторів на діяльність системи корпоративного управління.
CORPORATE GOVERNANCE OF HOLDING-TYPE AGRICULTURAL ENTERPRISES
The article summarizes the essence of the concept of "corporate governance" based on various interpretations. The theoretical foundations of corporate governance were studied and it was found that corporate governance is a widely researched field, and scientists have developed various definitions of this concept. It has been confirmed that in the context of integration and globalization trends, the importance of corporate governance is increasing, as the corporate form is a sought-after legal structure when choosing an organizational form of doing business, including in agriculture.With the emergence of corporations as a form of conducting business, the concept of "corporate management" arose.Success, development opportunities, investment attractiveness of the enterprise, additional guarantees for employees,partners, and customers depend on the quality of corporate management. It has been proven that the construction of an effective mechanism of corporate governance is a complex and multifaceted task that faces the management of existing and newly established enterprises, each of which is looking for ways to solve them. It was determined that agricultural enterprises of the holding type are such an organizational and legal form of conducting business, which allows to attract the maximum amount of resources for its development with almost no restrictions. The theoretical foundations of the development of corporate processes in the agricultural sector are considered. The importance of the agrarian corporate sector for the national economic complex of the country is substantiated. Structural elements of corporate management of holding-type agricultural enterprises are outlined. In order to form effective corporate management of agricultural enterprises of the holding type, it is proposed to apply the principles that provide for the formation of the goals and objectives of the analysis, the plan and the program for its implementation based on the selection of priority criteria and their indicators (regulated in regulatory documents and standards), taking into account the influence of external and internal factors on the activity of the corporate governance system.
Keywords: корпоративне управління; сільськогосподарське підприємство, агрохолдин-ги, нормативно-правова база, ефективність управління; corporate governance; agricultural enterprise, agricultural holdings, legal framework,governance efficiency